An Analytical Study of Concept of Sammasankappa in the Noble Eightfold Path of Theravada Buddhist Philosophy - Butsali, Phorncha; Chabutbuntrik, Wichian; Khathaisong, Banpot (Academic MCU Buriram Journal, 2023)
The purpose of this research were: 1) to study of Sammasankappa (Right Thought) in the Noble Eightfold Path of Theravada Buddhist Philosophy, 2) to analyze the concept of Sammasankappa (Right Thought) of Theravada Buddhist Philosophy and 3) to analyze an applying guideline the concept of Sammasankappa (Right Thought) of Theravada Buddhist Philosophy. This is a documentary research by collecting data from the Tripitaka, Commentary, academic documents on Buddhism and philosophy, and researches related to Sammasankappa (Right Thought). The research results found that: 1. Sammasankappa in the Eightfold Path of Theravada Buddhist Philosophy was mental process, consisted of 3 points: 1) Nekkhamma Sammasankappa (ill-advised intentions) or Nekkhamma-vitakka (thought freed from lust) was not immersed oneself with things satisfying various cravings; as it freed from sensuality or greed, 2) Abyapada Sammasankappa (Thoughts do not interfere with each other) or Abyapada-vitakka were considered as it freed form hatred, and 3) Avihimsa Sammasankappa or Avihisa-vitakka meant thought considered as it freed form anger. 2. To analyze the concept of Sammasankappa of Theravada Buddhist Philosophy was a starting point for practice. It was the result of a person's reasonable use of right views properly. It was considered as the starting point of idea, lead to verbal and physical action for the ultimate goal eliminated greed, hatred, and delusion. Those defilements clang in our mind. Practical principles should be conformed to the Threefold Learning and Mahasatipatthana Sutta (The sutra on the cultivation of mindfulness) should apply for practice in daily life. 3. To analyze an applying guideline the concept of Sammasankappa of Theravada Buddhist Philosophy divided into 2 ways: 1) using important virtues for living to increase our thought from sensual desires, called wisdom. The important virtue was to increase our thought with carelessness. We should endure. We should increase an important virtue for thought of non-exploit, 2) daily living under the Threefold Learning. We should comprise of precepts, concentration, and wisdom. And we should practice under Mahasatipatthana-Sutta with developing our mindfulness in daily life.